Adsorption of atrazine by laser induced graphitic material: An efficient, scalable and green alternative for pollution abatement. Issue 5 (October 2020) - Bayati, Mohamed; Numaan, Mohammed; Kadhem, Abbas; Salahshoor, Zahra; Qasim, Sally; Deng, Heng; Lin, Jian; Yan, Zheng; Lin, Chung-Ho; Fidalgo de Cortalezzi, Maria
Graphical abstract: Highlights: LIG was fabricated in a one-step, scalable, reagent-free process. LIG was evaluated for the first time as adsorbent of atrazine in water. The presence of humic acid decreased the adsorption of atrazine by 32 %. LIG exhibited high adsorption capacity over many previously reported adsorbents. LIG can be regenerated and reused for at least 4 cycles. Abstract: Laser induced graphitic material (LIG) was obtained from polyimide (PI) films using CO2 laser. This environmentally and economically promising fabrication method is a one-step, scalable, reagent-free process. LIG was fabricated, characterized, and tested as adsorbent for the removal of atrazine (ATZ) from water. The effect of presence of humic acid (HA), ionic strength (IS), adsorption time, initial ATZ concentration, and solution pH on the adsorption process was explored. The N2 Brunauer–Emmett–Teller (BET) surface area of LIG was 133.6 ± 1.7 m 2 /g. The prepared LIG exhibited significant removal of ATZ from aqueous solutions; hydrophobicity and π-π interactions played important roles in the process. Adsorption of ATZ on LIG followed a pseudo-second order kinetic model and Langmuir model for the isotherm with maximum adsorption capacity of 15.0 mg ATZ/g LIG. Adsorption was more favorable at higher pH and not affected by ionic strength. LIG exhibited enhanced performance over many previously reported adsorbents. The introduction stage of HA with respect to ATZ influenced the results: pre-introduction of HA reduced ATZ adsorption by 32 %, whereas post-introduction of HA resulted in a slight release of ATZ from the LIG.